PENGARUH KOMUNIKASI, DISIPLIN DAN LINGKUNGAN KERJA TERHADAP PRESTASI KERJA PADA PT. PERUM PERUMNAS MEDAN - Vibi alamsyah; Austin Alexander Parhusip (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2023)
Every company/organization will definitely face employment problems, one of which is how to enable the company's employees to work with good communication and high discipline, and create a comfortable work environment for employees to show their best performance. Even though it is recognized that non-human assets including nature still play an important role, without the support of quality human resources, everything will only be in vain. This study aims to determine the effect of communication, discipline and work environment on work performance at PT. National Public Housing Corporation. This type of research is quantitative research. The sample in this study amounted to 54 respondents who were taken using saturated sampling techniques. The results of this study indicate that partially the work environment has no effect and is not significant on work performance, while communication and discipline partially have a positive and significant effect on work performance. While simultaneously showing that communication, discipline, and the work environment together have a positive and significant effect on work performance.